Adopción de la segunda lengua, un componente de competitividad en la educación global - Hernandez Palma, Hugo Gaspar; Ojeda-Pertuz, Decireth del Carmen; Brito-Chiquillo, Johennys Genith (Colombian Applied Linguistics Journal, 2023)
Since 2009, the Ministry of National Education of Colombia has guided the construction and implementation of educational policies in early childhood and adolescence. These policies use an individualized approach as a strategy to provide the most vulnerable children under age 5 with access to suitable conditions and high-quality education. In order to enhance the quality of these educational policies at all levels basic, medium, and higher, the National Government has implemented a National Bilingualism Program (2004-2019). This project was launched by the Ministry of National Education to improve the competitiveness of Colombian citizens (Baron & Bonilla, 2011). Taking this purpose into account, this article presents some considerations on how to contribute to the aforementioned policy,promoting a competitive society and driving economic development in the country. The article highlights the fundamental role of bilingualism in the progress of a nation, drawing important observations from the analysis.